Systematic review on what works, what does not work and why of implementation of mobile health (mHealth) projects in Africa - Aranda-Jan, Clara B.; Mohutsiwa-Dibe, Neo; Loukanova, Svetla (BMC public health, 2014)
Access to mobile phone technology has rapidly expanded in developing countries. In Africa, mHealth is a relatively new concept and questions arise regarding reliability of the technology used for health outcomes. This review documents strengths, weaknesses, opportunities, and threats (SWOT) of mHealth projects in Africa.
Gesehen am 23.09.2020